2012
DOI: 10.1093/infdis/jis475
|View full text |Cite
|
Sign up to set email alerts
|

Hantaan Virus RNA Load in Patients Having Hemorrhagic Fever With Renal Syndrome: Correlation With Disease Severity

Abstract: To investigate the role of viral load in the pathogenesis of hemorrhagic fever with renal syndrome, the Hantaan virus RNA load in plasma from 101 patients was quantified, and the relationships between viral load and disease course, severity, and level of specific humoral immunity were analyzed. The viral load, detectable in 79 patients, ranged from 3.43 to 7.33 log10 copies/mL of plasma. In the early stage of disease, patients in severe/critical group were found to have higher viral loads than those in the mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 12 publications
4
49
0
1
Order By: Relevance
“…Our results clearly show that the HFRS incidence in China have decreased dramatically in during the last decade, which is similar to the general trend in several countries in Asia, as far back as 1920s to 1930s, China witnessed the prevalence of HFRS. The targeted vaccine development has lasted for decades since the isolation of the Hantaan virus at home and abroad in 1980 successively; after almost 20 years of efforts, multiple HFRS-targeted vaccines which have played an important role in the control of HFRS in China, have been developed2122. Currently, the prevention and treatment of HFRS in China follows the principle of “three-early and one-in-place”, namely, early discovery, early rest, early treatment and in-place isolation treatment, and it renders great progress in the prevention of HFRS, but it is still faced with challenges, with the implementation of NHFPC’s National HFRS monitoring program (Trial) since 2005, the disease incidence detected in most provinces showed significant decrease as in some previous studies2324.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly show that the HFRS incidence in China have decreased dramatically in during the last decade, which is similar to the general trend in several countries in Asia, as far back as 1920s to 1930s, China witnessed the prevalence of HFRS. The targeted vaccine development has lasted for decades since the isolation of the Hantaan virus at home and abroad in 1980 successively; after almost 20 years of efforts, multiple HFRS-targeted vaccines which have played an important role in the control of HFRS in China, have been developed2122. Currently, the prevention and treatment of HFRS in China follows the principle of “three-early and one-in-place”, namely, early discovery, early rest, early treatment and in-place isolation treatment, and it renders great progress in the prevention of HFRS, but it is still faced with challenges, with the implementation of NHFPC’s National HFRS monitoring program (Trial) since 2005, the disease incidence detected in most provinces showed significant decrease as in some previous studies2324.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, HTNV RNA could be detected in the plasma of HFRS patients only at 3 to 12 days after the onset of the disease, and the viral load gradually decreased to an undetectable level with the course of the disease, which is in accordance with the self-limiting properties of HFRS. There is a statistically significant association between plasma HTNV RNA load in the early stage and disease severity in patients, but there is no relationship between HTNV RNA load and the peak value of the titers of HTNV NP-specific IgM and IgG (17). Our previous studies also showed that the magnitude of the cellular immune response and the frequency of the epitope-specific pentamer-positive CD8 ϩ T cell response were much higher in patients with mild/moderate HFRS than in those with severe/critical disease at the acute stage of the disease.…”
Section: Discussionmentioning
confidence: 90%
“…However, no significant difference was found between the severe/critical group and the mild/moderate group (1894.31 ng/mL vs. 1957.78 ng/mL; p = 0.86, Figure 2E) in the oliguric stage. We also analyzed the relationship between plasma cf-DNA values in febrile/hypotensive stages and the viral load, which was reported to correlate positively with disease severity [2], and found that there is a significant positive correlation of plasma cf-DNA levels with viral load ( p ˂ 0.001, R = 0.68, Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory tests included blood platelets (×10 9 /L), serum creatinine level (μmol/L) and white blood cell count (×10 9 /L). The viral load data were also available from the study we had recently performed [2]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation